PRIMARY PULMONARY HYPERTENSION IN PREGNANCY: A CASE REPORT AND ANESTHETIC IMPLICATIONS - Hayak Pereira Lopes, Maykon (Health and Society, 2025)
Pulmonary arterial hypertension (PAH) is a rare and serious condition, especially during pregnancy, with an increased risk of maternal and fetal morbidity and mortality. We report the case of a pregnant woman with an echocardiographic diagnosis of PAH in hemodynamic decompensation who underwent cesarean section under continuous epidural anesthesia. We describe the anesthetic approach, maternal and neonatal outcomes, and discuss the anesthetic implications of PAH during pregnancy, with an emphasis on hemodynamic monitoring and management. This case illustrates the importance of individualized anesthetic treatment and intensive surveillance in these high-risk scenarios.